Experimental evolution of the megaplasmid pMPPla107 in Pseudomonas stutzeri enables identification of genes contributing to sensitivity to an inhibitory agent. (17th January 2022) - Smith, Brian A.; Dougherty, Kevin; Clark, Meara; Baltrus, David A.
Abstract : Horizontally transferred elements, such as plasmids, can burden host cells with various metabolic and fitness costs and may lead to other potentially detrimental phenotypic effects. Acquisition of the Pseudomonas syringae megaplasmid pMPPla107 by various Pseudomonads causes sensitivity to a growth-inhibiting substance that is produced in cultures by Pseudomonads during growth under standard laboratory conditions. After approximately 500 generations of laboratory passage of Pseudomonas stutzeri populations containing pMPPla107, strains from two out of six independent passage lines displayed resistance to this inhibitory agent. Resistance was transferable and is, therefore, associated with mutations occurring on pMPPla107. Resequencing experiments demonstrated that resistance is likely due to a large deletion on the megaplasmid in one line, and to a nonsynonymous change in an uncharacterized megaplasmid locus in the other strain. We further used allele exchange experiments to confirm that resistance is due to this single amino acid change in a previously uncharacterized megaplasmid protein, which we name SkaA. These results provide further evidence that costs and phenotypic changes associated with horizontal gene transfer can be compensated through single mutational events and emphasize the power of experimental evolution and resequencing to better understand the genetic basis of evolved phenotypes. This article is part of the theme issue 'The secret lives of microbial mobile genetic elements'.